2018
DOI: 10.3390/app8020203
|View full text |Cite
|
Sign up to set email alerts
|

Nozzle Printed-PEDOT:PSS for Organic Light Emitting Diodes with Various Dilution Rates of Ethanol

Abstract: Abstract:In this study, we investigated the ink formulation of poly (3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) as the hole injection layer (HIL) in an organic light emitting diode (OLED) structure. Generally, in a PEDOT:PSS solution, water is incorporated in the solution for the solution process. However, the fabrication of thin film which contained the water, main solvent, could not easily form by using printing technology except spin-coating process because of the high surface tension o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Among those of the applications, there have been many researches to study fabrication of flexible OLEDs using printing technologies such as inkjet printing [6], aerosol jet [7], screen printing [8], electrohydrodynamic jet [9] and nozzle jet printing [10]. Nozzle jet printing is a continuous jetting technique that utilizes constant air pressure with flow pump.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…Among those of the applications, there have been many researches to study fabrication of flexible OLEDs using printing technologies such as inkjet printing [6], aerosol jet [7], screen printing [8], electrohydrodynamic jet [9] and nozzle jet printing [10]. Nozzle jet printing is a continuous jetting technique that utilizes constant air pressure with flow pump.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…Inkjet printing allows for a low-cost fabrication with a relatively high accuracy, whereas capillary action could be used to make pump-free microfluidic devices on paper-based substrates; therefore, authors concluded, with further progress in the field of printed electronics, the inkjet-printed and paper-based low-cost sensors would be implemented in near future. Another application for OLED was presented with nozzle-printed PEDOT:PSS by Yoon et al [9]. They investigated the influence of mixing ratio of ethanol to PEDOT:PSS on the quality of nozzle-printed patterns and eventually the performance of OLED device which used the diluted PEDOT:PSS as a hole injection layer.…”
Section: Printed Electronicsmentioning
confidence: 99%
“…The feasibility of inkjet printing technology in the production of printed displays has been verified by applying such technology in the laboratory. For example, the hole injection layer 5 (HIL), hole transport layer 6 (HTL), emission layer 7 (EML), and thin film encapsulation 8 (TFE) layer of OLEDs have been prepared by printing.
Figure 1 Simplified diagram of the OLED structure and production flow.
…”
Section: Introductionmentioning
confidence: 99%